Tungsten Nanoparticles Accelerate Polysulfides Conversion: A Viable Route toward Stable Room‐Temperature Sodium–Sulfur Batteries. Issue 11 (8th February 2022) - Liu, Yuping; Ma, Shuangying; Rosebrock, Marina; Rusch, Pascal; Barnscheidt, Yvo; Wu, Chuanqiang; Nan, Pengfei; Bettels, Frederik; Lin, Zhihua; Li, Taoran; Ge, Binghui; Bigall, Nadja C.; et al.
Abstract: Room‐temperature sodium–sulfur (RT Na–S) batteries are arousing great interest in recent years. Their practical applications, however, are hindered by several intrinsic problems, such as the sluggish kinetic, shuttle effect, and the incomplete conversion of sodium polysulfides (NaPSs). Here a sulfur host material that is based on tungsten nanoparticles embedded in nitrogen‐doped graphene is reported. The incorporation of tungsten nanoparticles significantly accelerates the polysulfides conversion (especially the reduction of Na2 S4 to Na2 S, which contributes to 75% of the full capacity) and completely suppresses the shuttle effect, en route to a fully reversible reaction of NaPSs. With a host weight ratio of only 9.1% (about 3–6 times lower than that in recent reports), the cathode shows unprecedented electrochemical performances even at high sulfur mass loadings. The experimental findings, which are corroborated by the first‐principles calculations, highlight the so far unexplored role of tungsten nanoparticles in sulfur hosts, thus pointing to a viable route toward stable Na–S batteries at room temperatures. Abstract : A sulfur host material based on tungsten nanoparticles (with an average size of about 1.5 nm) embedded in nitrogen‐doped graphene is demonstrated (W@NG), when used in room‐temperature sodium–sulfur batteries, the W@NG can significantly accelerate the polysulfides conversion and completely suppress the shuttle effect, thus contributing to the unprecedented specific capacity, rate capability, and cycling stability.